Fabrication of Mg-Al Layered Double Hydroxide Thin Membrane for All-Solid-State Alkaline Fuel Cell Using Glass Paper as a Support - Kubo, Daiju; Tadanaga, Kiyoharu; Hayashi, Akitoshi; Tatsumisago, Masahiro (Frontiers in Materials, 2020)
Layered double hydroxides (LDHs) are promising solid electrolytes for all solid-state alkaline fuel cells (AFCs) because of inorganic clay-like materials. However, LDHs were usually obtained as powder, and the formation of thin membranes as a separator of a fuel cell is rather difficult. In this study, a glass paper, non-woven fabric of fine glass fibers with more than 90% porosity, was used as a support for Mg-Al LDH powder, and self-standing, thin membranes for all solid-state AFCs were fabricated. Crystals of Mg-Al LDH were deposited in the inside of the glass paper by repeated immersion in Mg-Al LDH-dispersed solution and drying. Thickness of the obtained Mg-Al LDH thin membrane was about 150 µm, and LDH layer showed c-axis orientation because of the plate-like structure. The H2-O2 fuel cell using the Mg-Al LDH thin membrane as an electrolyte showed open circuit voltage of more than 0.9 V, indicating that the Mg-Al LDH thin membrane is dense and has high gas barrier property. The H2-O2 fuel cell using the Mg-Al LDH thin membrane showed higher power density compared with that using pelletized Mg-Al LDH powder as the electrolyte. The glass paper is proved to be very effective support for making thin Mg-Al LDH electrolyte membrane.